Is ectopic Cushing’s syndrome underdiagnosed in patients with small cell lung cancer? - Piasecka, Marta; Larsson, Martin; Papakokkinou, Eleni; Olsson, Lena; Ragnarsson, Oskar (Frontiers in Medicine, 2022)
Introduction: Ectopic Cushing’s syndrome (ECS) is an uncommon disorder. Recently, however, a larger proportion of patients with endogenous Cushing’s syndrome (CS) had ECS than has previ-ously been reported. Objective: The aim of this study was to determine whether ECS is an underdiagnosed disorder in patients with small-cell lung cancer (SCLC). Methods: Medical records from consecutive patients diagnosed with SCLC at our hospital be-tween 2013 and 2019 were reviewed (N=213; mean age 69.5 ± 9 years; range, 36-89 years). The probability of having ECS was evaluated by review of biochemical and clinical features, including presence of recent onset diabetes mellitus, therapy resistant hypertension and/or spontaneous hypokalaemia. Results: Of 213 identified patients with SCLC, one (0.5%) patient had confirmed ECS, two (1%) patients had probable ECS, and twenty-three (11%) patients had possibly ECS. Patients with SCLC and possibly or probable ECS exhibited a significantly shorter survival than patients only with SCLC (8 months vs 14 months, respectively). Conclusions: Our findings indicate that ECS is underdiagnosed in patients with SCLC. Given the serious consequences of untreated ECS, the low detection rate highlights the need to improve en-docrine work-up of patients with SCLC who present with biochemical and clinical features associ-ated with ECS. Prospective studies are needed to establish a reliable assessment of the incidence of ECS and to optimize early detection strategies.